Coherent Mortality Forecasting for the Algerian Population - Flici, Farid (Assurances et gestion des risques / Insurance and Risk Management, 2021)
Mortality forecasting is much needed for population projections and actuarial calculations. Forecasting mortality of males and females in an independent way leads in most of cases to some incoherence regarding the expected male-female mortality evolution. To avoid a possible unrealistic convergence/divergence in this sense, a coherent mortality forecasting is required. In this paper, we compare the performance of two coherent models, namely the model of Li and Lee (2005) and that of Hyndman et al. (2013) on forecasting male and female mortality of the Algerian population. Results show that the first model provides better goodness-of-fit but less coherence compared to the second one.